Composition and the predicted functions of fungal communities and the key drivers in acidic soils of Jiaodong Peninsula, China - Liu, Jing; Wazir, Zafran Gul; Hou, Guoqin; Wang, Guizhen; Rong, Fangxu; Xu, Yuzhi; Liu, Kai; Li, Mingyue; Liu, Aiju; Liu, Hongliang; Sun, Hongwen (Frontiers in Microbiology, 2025)
IntroductionSoil acidification imperils soil health and hinders the agricultural sustainability. As being more tolerant than bacteria to soil acidification, so it would be more meaningful for agricultural management and crop yield to characterize fungal community in acidic soils and manifest its key drivers.MethodThis study investigated the composition and diversity of fungal communities and its key driving factors by collecting 90 soil samples from the acidic region of Jiaodong Peninsula China, spanning 3 × 104 km2.ResultsThe results indicated that most soil pH values ranged from 5.01 to 6.42, and the exchangeable acidity (EA) content raised significantly (p < 0.01) along with soil acidic degree increasing. However, no significant differences were found in fungal community diversity and composition among various soil samples, which were all predominantly habited with the phyla of Ascomycota and Basidiomycota. Results of the linear discriminant analysis effect size (LEfSe) analysis revealed that saprophytic fungi were biomarkers of the slightly acidic soil (pH 6.0–6.5), including Nectriaceae, Thielavia, Nectria, Haematonectria, and unclassified Microascaceae, while plant pathogenic fungi, such as Didymellaceae, were biomarkers of the soils pH < 5.5. Similarly, the FUNGuild results also indicated that saprophytic fungi and pathogenic fungi were the dominant functional guilds in the investigated acidic soils, accounting for 66% of the total fungal communities. Redundancy analysis (RDA) revealed that soil pH as well as nitrate nitrogen (NO3−-N) and total nitrogen (TN) significantly associated with fungal community at the phylum level, whilst soil pH was the only factor significantly linked to individual fungal classes (p < 0.01 or 0.05). The further Mantel test analysis and structural equation modeling (SEM) suggested that, in contrast to the negative and directive driving of soil pH on fungal communities' variation, the specific plant pathogenic fungi, Gibberella and Didymellaceae, were significantly and positively associated with soil acidic characteristics (p < 0.05).DiscussionThese findings highlighted that, in addition to modulating the variation of soil fungal community, soil acidification might prime some plant pathogens development. So that, more attentions should be focused on impact of soil acidification on fungal ecology, as well as plant pathogenic fungi.